Minat Siswa Terhadap Pembelajaran Seni Budaya Di SMA Negeri 1 SUMBAR - Devina Sari; Marzam Marzam (SENDRATASIK UNP, 2020)
This study aims to determine students’ interest inmusical art learning and what factors that influence students' interest in musical art learning in SMA Negeri 1 Sumatra Barat.This type of studywas a qualitative with using a descriptive approach. The main instrument in this study was the researcher. It was assisted by supporting instruments such as stationery and camera. Techniques of Data collection were carried out by taking literature study, observation and interview. The analysis process was startedby analyzing data and seleceting selectively, then the data were displayed in a descriptive form.The result shows that the lack of students’ interest occur inmusical art learning in SMAN Sumatra Barat. The cultural art teacher in the learning process does not understand the learning material and the teaching method is not variative. The Factors that influence students' interest in learning at SMAN 1Sumatra Barat in the subject of musical art are internal and external factors.